Coffee Cultivation and Industry in Brazil: A Comprehensive Review - Julio Vartan (International Journal of Science and Society, 2023)
Brazil is renowned as the world's largest producer and exporter of coffee, playing a pivotal role in the global coffee industry. This article provides a comprehensive review of coffee cultivation, processing, and the coffee industry in Brazil. It examines the historical context, geographical factors, economic significance, and environmental impact of coffee production in the country. The article also explores the challenges faced by the Brazilian coffee industry, such as climate change, sustainability issues, and market fluctuations. Through an in-depth analysis of the Brazilian coffee sector, this study contributes to a better understanding of the complexities and dynamics of coffee production in one of the most significant coffee-producing nations.